Resveratrol: brain effects on SIRT1, GPR50 and photoperiodic signaling - Leheste, Joerg R.; Torres, German (Frontiers in Molecular Neuroscience, 2015)
SIRT1 deacetylase, a sensor of intermittent energy restriction, is inextricably intertwined with circadian regulation of central and peripheral clock genes. The purpose of this study was to identify SIRT1-specific target genes that are expressed in a circadian rhythm pattern and driven, in part, by specific components of foodstuffs. Using human cells and rats fed with a resveratrol diet we show that SIRT1 binds to, and transcriptionally regulates, a gene locus encoding the G protein-coupled receptor, GPR50 in the brain. GPR50 is the mammalian orthologue of the melatonin1c membrane-bound receptor which has been identified as a genetic risk factor for bipolar disorder and major depression in women. In general, our findings support and expand the notion that circadian clock signaling components and dietary interventions are adaptively linked, and suggest that the brain may be particularly sensitive to metabolic events in response to light-dark cycles.